Hubungan Jarak Aliran Air Lindi Terhadap Kualitas Air Tanah Dan Tindakan Masyarakat di Sekitar TPA Ciangir Kota Tasikmalaya - Thyasz Spica Nurlestari; Diana Retna Utarini Suci Rahayu; Imam Santosa (Publikasi Indonesia, 2026)
The increase in the volume of waste at the Ciangir Landfill (open dumping system) has the potential to contaminate groundwater through leachate water. The distance of leachate flows is thought to determine the level of contamination, while community responses to changes in water quality have not been fully rational and adaptive. This research aims to analyze the relationship between leachate flow distance and groundwater quality, the effect of groundwater quality on community actions, and the simultaneous influence of leachate flow distance and groundwater quality on community actions around the Ciangir Landfill, Tasikmalaya City. Explanatory quantitative research with a cross-sectional approach was conducted on 35 wells dug within a radius of 1 km using stratified random sampling. Data were collected through laboratory tests (E. coli, Total Coliform, pH, BOD, COD, TSS), field observations, and questionnaires based on Max Weber's social action theory. The analysis used correlation tests, Chi-Square, and binary logistics regression at a significance rate of 95%. A total of 48.6% of groundwater did not meet the requirements, and 68.6% did not meet bacteriological standards. There was a significant relationship between well distance and Total Coliform (p=0.009) and between groundwater quality and community actions (p=0.006). Simultaneously, leachate flow distance and groundwater quality had a significant effect on community actions with a contribution of 38.8% to the model explanation and 80% classification accuracy. The distance of leachate flow and groundwater quality play a significant role in shaping community actions. The variable distance of leachate flow is the dominant factor, so strengthening the landfill management system and increasing community environmental literacy is an urgency to minimize health risks